Cloning and expression of fusion (F) and haemagglutinin-neuraminidase (HN) genes of Newcastle disease virus in insect host (Sf9cells) - GOWRAKKAL, MAHESWARAPPA; VIJAYARANI, K; KUMANAN, K (The Indian Journal of Animal Sciences, 2014)
The lentogenic strain of Newcastle disease virus (NDV) was propagated in 9–11 day-old specific pathogen free (SPF) embryonated chicken eggs. Allantoic fluid was collected after the death of embryo, the obtained allantoic fluid showed virus titre (HA) of 1:256. Viral RNA was extracted from allantoic fluid by Trizol method, complementary RNA was synthesized by reverse transcriptase enzyme (superscript-III) and full length recombinant fusion and recombinant haemagglutinin- neuraminidase gene was amplified by PCR using gene specific primers. Gel purified PCR products were cloned into pTriEx neo 1.1 expression vector and transformed into E. coli BL-21 DE3 cells. The presence of insert in recombinant colonies was confirmed by colony PCR, restriction digestion and sequencing of insert released products. Cloned recombinant plasmids of fusion and haemagglutinin neuraminidase genes were expressed in Sf9 cells using baculovirus expression vector system. After 72 h of transfection plaque assay was done to confirm the presence of recombinant virus and then positive recombinant viruses were transfected to insect cells. The expression of recombinant proteins in Sf9 cells was confirmed by sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS- PAGE), immunoblotting and immunofluorescent assays (IFA).